Hemifacial Display of Emotion in the Resting State - M. K. Mandal; H. S. Asthana; S. K. Madan; R. Pandey (Behavioural Neurology)
The human face at rest displays distinguishable asymmetries with some lateralization of emotion or expression. The asymmetrical nature of the resting face was examined by preparing hemifacial composites, left–left, right–right, along with normal facial orientation. The left side and right side composites were constructed by using the lateral half of one side of the face and its mirror-reversal. The left side facial composites were found to be more emotional than the right side or normal facial orientations of neutral expressions.